The Influence of Self Efficacy and Locus of Control on Employee Work Productivity (Study at PT Perkebunan Nusantara IV Adolina) - Tri Danica Sinaga; Nicholas Marpaung (Journal of Finance and Business Digital, 2023)
Employee efficiency can be evaluated by examining characteristics that influence productivity, such as self-efficacy and Locus of Control. This article is to explain or describe a symptom or event to assess the extent to which self-efficacy and Locus of Control influence employee productivity at Adolina IV PTPN. This research approach uses data collection techniques and quantitative data analysis to test the relationships between variables. This research involved 48 PTPN IV Adolina personnel who were selected selectively. This research data analysis was carried out through several stages, namely instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that self-efficacy and Locus of Control have a significant positive influence on employee productivity, both partially and simultaneously.